A medical thermal imaging device for the prevention of diabetic foot ulceration. (3rd February 2017) - Machin, G; Whittam, A; Ainarkar, S; Allen, J; Bevans, J; Edmonds, M; Kluwe, B; Macdonald, A; Petrova, N; Plassmann, P; Ring, F; Rogers, L; et al.
Abstract: In this paper a description is given of the development, characterisation and first results of a thermal imaging device aimed at significantly reducing the incidence of diabetic foot ulceration (DFU). These devices will be used in three clinical centres and in two preliminary clinical trials. The first will be on healthy volunteers to set a robust baseline for the overall research aims and the second on >100 patients at high risk of DFU. In the second phase of the project the objective is to demonstrate significant reduction in the incidence of DFU through a comparison of the results of standard care of high risk feet with standard care plus thermal imaging.